Streptomyces sp. 1S1 isolated from Southern coast of the Red Sea as a renewable natural resource of several bioactive compounds - Azal A. Mothana; Hassan A. Al-Shamahy; Ramzi A. Mothana; Jamal M. Khaled; Adnan J. Al-Rehaily; Abdullah Y. Al-Mahdi; Ulrike Lindequist (Elsevier, 2022)
Red Sea represents one of the most remarkable marine ecosystems. However, it is also one of the world's least explored areas of marine biodiversity. The aims of this investigation were therefore, to isolate marine microorganisms from the seashore sediments and water in shallow region from west Yemen coast, to assess their antimicrobial potential, to identify the highly active isolate, and to purify and identify the bioactive compounds from it. In this regard, twenty-five bacterial strains have been isolated from twenty samples and tested for their antimicrobial ability against some pathogenic bacteria and yeast by using the agar disk diffusion and agar well diffusion assay. Out of the total 25 marine actinomycetes isolates only 13 exhibited interesting antimicrobial activity. The morphological, biochemical, and phylogenetic characteristics of the potential isolate 1S1 were compatible with their classification in the genus Streptomyces. The 16S rRNA gene sequences have shown that the isolate 1S1 clustered with Streptomyces longisporoflavus. The strain Streptomyces sp. 1S1 was cultivated and extracted with ethyl acetate. The GC-MS study of the extract indicated the presence of certain fatty acyl compounds e.g., tetradecanoic acid, 9-octadecenoic acid, hexadecanoic acid, and 9,12,15-octadecatrienoic acid. Using chromatographic techniques, three compounds were isolated and by spectroscopic methods e.g., IR, MS and NMR structurally elucidated. The three compounds were identified as a triacylglyceride, 9-octadecenoic acid, and hexadecanoic acid. The study reinforces the evidence of the potential of Streptomyces sp and the ability to produce several antimicrobial compounds.